Antecedents toward the Purchase Intention among Sarawakian Young Smart phone Users - Irene Kho; Ting Hui Bun; Pang Wei Chao; Mark Kasa (International Journal of Supply Chain Management, 2018)
The vast technological development has been widely accepted by consumers, prevalently seen through the popularity and mass use of smart phones. This scenario posed a challenge to the smart phone operators and companies, in order to retain their existing smart phone users; while at the same time, attracting the often unpredictable, young potential consumers.Hence, this study investigated the relationship between the antecedents (features, brand, price, social influence, and advertising) and purchase intention towards smart phones, with the focus on young consumers. Paper questionnaires were distributed through convenience sampling, andmultiple linear regressions were implemented for the data analysis. The results revealedthat brand, social influence, and advertising are related to purchase intention. On the contrary, features and price were discovered to be not related to purchase intention. Hence, industry practitioners, especially smart phone companies and providers, should consider these antecedents to aid their sales effort for future business sustainability.